DATA PROCESSING APPLICATIONS OF ZAKAT FITRAH USING MICROSOFT VISUAL BASIC 6.0 - Rani Sutarbin; Rahayu Noveandini, Skom., MM Rahayu Noveandini, Skom., MM (Jurnal Sistem Informasi, 2005)
In the holy month of Ramadan are obligatory acts of worship that should be done byMuslims, one of which is to perform Zakat Fitrah. Tithe is prescribed as the end ofRamadan, aims to rid themselves of the things that littered the fast and compensationfor those needy and poor. In the process of tithe payments are collecting zakatcommittee consisting of the Amil Zakat, Amil trusted to receive and collect all thealms that have been paid by the giver of zakat (Muzaki), and distribute to therecipient entitled to zakat (Mustahiq). But in its implementation in the field, the AmilZakat is still often confronted by various difficulties one of them is in terms of dataprocessing is still a lot of charity because the Zakat committees who use the manualway of bookkeeping so that in the process of making reports, they will have trouble ifthe amount of data collected has reached a maximum intensity of the ability of theAmil Zakat is required a high level of accuracy in data processing in order to producegood and accurate information. From the issues above authors would like to try toprovide solutions to the Zakat committees, particularly in the Masjid Al Istiqomahlocated in the area Cireundeu Ciputat Raya through applications made by the author,in the hope that these difficulties can be overcome with good so that the process ofcollecting and distributing Zakat Fitr to persons entitled to be running smoothly andon time.